2005
DOI: 10.1097/01.ta.0000066381.33339.c0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Aeromonas hydrophila and Vibrio alginolyticus Isolated from a Wound Infection: A Case Report

Abstract: Aeromonas hydrophila is a motile, nonsporulating, fermentative, facultative, anaerobic, gram-negative bacillus commonly found in fresh water, tap water, soil, and swimming pools. 1,2 Human infections caused by Aeromonas spp. are frequently associated with trauma in the aquatic environment, 3-7 immunosuppression, 7 and chronic disease. 8 ␤-Lactam resistance in Aeromonas spp. has been reported. 9 In clinical Aeromonas isolates, genetic properties of the ␤-lactamase genes have been characterized. 9 -12 Previous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…With PCR methods, it is possible to detect most species of pathogens in a wound in a matter of hours rather than days. PCR has already shown promise in various clinical situations, including identifying antibiotic-resistant gram-negative organisms (20), bacteria that elaborate neurotoxins (21) or other virulence factors (22), and slow-growing organisms like mycobacteria (23). Additionally, previous antibiotic therapy would be much less likely to cause false-negative results than with a standard culture.…”
Section: E D I T O R I a L S E D I T O R I A Lmentioning
confidence: 99%
“…With PCR methods, it is possible to detect most species of pathogens in a wound in a matter of hours rather than days. PCR has already shown promise in various clinical situations, including identifying antibiotic-resistant gram-negative organisms (20), bacteria that elaborate neurotoxins (21) or other virulence factors (22), and slow-growing organisms like mycobacteria (23). Additionally, previous antibiotic therapy would be much less likely to cause false-negative results than with a standard culture.…”
Section: E D I T O R I a L S E D I T O R I A Lmentioning
confidence: 99%
“…Several studies have documented the antibiotic resistance profile of Aeromonas hydrophila. 15,16 Therefore, recommended antibiotics to treat this organism include intravenous fluoroquinolones or a third-or fourth-generation cephalosporin. 17 This organism is known to cause severe wound infections and to compromise revascularized limbs when these injuries are sustained in an aquatic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, A. hydrophila is the predominant strain in clinical samples, which can prove the role it can play in pathogenesis. Therefore, it deserves even more attention (Garibay et al, 2006;Horii et al, 2005;Pokhrel and Thapa, 2004). In this study, the predominant species in minced meat was A. hydrophila (59%) followed by A. caviae (20.6%), A. sobria (17%), A. jandaei (3.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, motile Aeromonas species were present in all samples including retail lamb meat and offal; so it was concluded that meat products were potentially significant sources of virulent Aeromonas species and might play an important role in the etiology of Aeromonas gastroenteritis (Majeed et al, 1989). Aeromonads had been regarded as controversial pathogens; however, recent investigations have indicated some strains are entropathogenic (Garibay et al, 2006;Horii et al, 2005;Pokhrel and Thapa, 2004;Sinha et al, 2004;Soltan Dallal and Moezardalan, 2004;Vila et al, 2003). Of the various virulence factors described to explain the pathogenicity of Aeromonas species, beta hemolytic activity seems to be related to enterotoxigenicity (Chopra et al, 1991;Wong et al, 1998).…”
Section: Introductionmentioning
confidence: 99%